Development of The Merdeka Curriculum Teaching Module based on the Local Wisdom of Bondowoso Batik - Hasanah, Rafiatul; Rasyid, Aulia Nur (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2024)
The aim of this research is to develop an Merdeka curriculum teaching module for the science and science project subject matter of substances and changes based on the local wisdom of Bondowoso Batik at SMK Negeri 1 Tamanan and to find out the responses of practitioners and students to the teaching module developed. This research uses Research and Development research, with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. The subjects in this research were 33 students in class X Craft Design and Production at SMK Negeri 1 Tamanan. The results of data analysis in this research show that the development of teaching modules for the Social Science Project subject based on the local wisdom of Bondowoso Batik is valid, very good, and very interesting to increase student interest. This is proven by: (1) The validation results of the material expert obtained a score of 93.84% which was included in the